Evaluating the role of serum cystatin C as a circulating biomarker of diabetic retinopathy from a rural Indian population - Keerthana Raghu; R. Janani Surya; Chitaranjan Mishra; Karan Singh; Nabatika Mohanty; Jitendra Kumar Sahoo; Shiva Prasad Sahoo; Ashok Kumar Singh; Rajiv Raman (Taiwan Journal of Ophthalmology, 2024)
PURPOSE: This study aimed to evaluate serum cystatin C as a potential biomarker for diabetic retinopathy (DR) in a rural Indian population, addressing the urgent need for effective screening tools amidst rising diabetes prevalence. MATERIALS AND METHODS: A cross-sectional study recruited 112 patients with diabetes mellitus from Sambalpur, Odisha, India, categorized into groups with and without DR. Serum cystatin C levels were measured alongside clinical and demographic parameters, using established diagnostic methods. RESULTS: Patients with DR exhibited significantly higher serum cystatin C levels compared to those without DR (mean: 0.99 ± 0.50 mg/L vs. 0.80 ± 0.36 mg/L, P = 0.027). Adjusted analysis showed a notable association between higher cystatin C tertiles and DR (adjusted odd’s ratio: 7.65, 95% confidence interval: 1.49–39.08, P = 0.01), highlighting its potential as an independent predictor. CONCLUSION: Elevated serum cystatin C levels were strongly associated with the presence of DR, suggesting its utility as a biomarker for early identification and risk stratification in diabetic patients. Integration of cystatin C measurement into routine clinical practice may enhance DR screening and management strategies, offering potential benefits in reducing vision loss and improving patient outcomes. This study underscores the need for further longitudinal research to validate these findings and elucidate the temporal relationship between cystatin C levels and DR progression.